KANDUNGAN LOGAM BERAT Pb PADA AIR LAUT, SEDIMEN DAN DAGING KERANG LORJUK (Solen sp.) DI PANTAI MADURA - Ninis Trisyani (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTThe accumulation of the heavy metal lead (Pb) into the shells can be through the food network or contact with the environment. This study aims to determine the content of heavy metal Pb in water, sediment and Bamboo Scallops meat (Solen sp.). This research was conducted in March - May 2019 on the beaches of Kwanyar Bangkalan and Talang Siring Pamekasan, Madura. The content of heavy metal Pb in water, sediment and Bamboo Scallops (Solen sp.) Samples was analyzed using the Atomic Absorption Spectro-photometer (AAS) method. In the aquatic environment, water quality measurements are carried out including salinity, temperature, pH and current. The results showed that the concentration of heavy metal Pb in the water at Kwanyar Beach was not measured, and at Talang Siring Beach was 0.13 ml / l in March, 0.10 mg / l in April and not measured in May. The Pb content in sediment at Kwanyar Beach in March was 51.04 mg / kg, April 6.11 mg / kg and 9.78 mg / kg in May, and at Talang Siring Beach in March was 72.05 mg / kg, April 3.73 mg / kg and May 2.50 mg / kg. Pb content in Bamboo Scallops meat was not measured at both beaches during the observation. The results showed that the heavy metal Pb in Bamboo Scallops meat was still below the quality standard and safe for consumption.Key words: Heavy metal Pb, Lorjuk, Solen sp. Madura BeachABSTRAKAkumulasi logam berat Timbal (Pb) ke dalam tubuh kerang dapat melalui jaringan makanan atau kontak dengan lingkungan. Penelitian ini bertujuan untuk mengetahui kandungan logam berat Pb pada air, sedimen dan daging kerang bambu (Solen sp.). Penelitian ini dilakukan pada bulan Maret – Mei 2019 di pantai Kwanyar Bangkalan dan Talang Siring Pamekasan, Madura. Kandungan logam berat Pb pada sampel air, sedimen dan kerang bambu (Solen sp.) dianalisis dengan menggunakan metode Atomic Absorption Spectro-photometer (AAS). Pada lingkungan perairan dilakukan pengukuran kualitas air meliputi salinitas, suhu, pH dan arus. Hasil penelitian menunjukkan bahwa konsentrasi logam berat Pb pada air di Pantai Kwanyar tidak terukur, dan di Pantai Talang Siring sebesar 0,13 ml/l pada bulan Maret, 0,10 mg/l pada bulan April dan tidak terukur pada bulan Mei. Kadar Pb pada sedimen di Pantai Kwanyar bulan Maret sebesar 51,04 mg/kg, April 6,11 mg/kg dan Mei 9,78 mg/kg, dan di Pantai Talang Siring pada bulan Maret sebesar 72,05 mg/kg, April 3,73 mg/kg dan Mei 2,50 mg/kg. Kadar Pb di daging kerang bambu tidak terukur di kedua pantai selama pengamatan. Hasil penelitian menunjukkan logam berat Pb pada daging kerang bambu masih dibawah batas baku mutu dan aman dikonsumsi.Kata kunci: Logam berat Pb, Lorjuk, Solen sp. Pantai Madura